Designing PMRI-Based Learning Materials Using the ADDIE Model to Enhance Conceptual Understanding of π (Pi) in Circle Topics - Muhammad Assegaf Baalwi; Wahyu Maulida Lestari; Masyitah Noviyanti (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
This article is about developing mathematics learning materials related to the Indonesian Realistic Mathematics Education (PMRI) approach for teaching the circle topic, with a focus on enhancing sixth-grade students’ conceptual understanding of π (Pi) at MI Ma’arif Pagerwojo. The development followed the ADDIE instructional design model. The research instruments included expert validation sheets, lesson implementation observation sheets, response questionnaires, and achievement tests. Based on expert validation, two validators rated the teaching module at 95.5% and 92.6%, the student worksheet (LKPD) at 91.6% and 94%, and the learning outcome test at 85% and 90% all falling within the "highly valid" category. Observation results of lesson implementation by both teacher and students yielded scores of 90% and 87.5%, respectively, while teacher and student response questionnaires reached 93.7% and 87%. It shows that the developed learning materials are highly practical. The effectiveness also has been proved, as 80% of students met the minimum mastery criterion (KKM), satisfying the criterion for classical completeness. These findings demonstrate that PMRI-based materials effectively facilitate students’ meaningful understanding of π through contextual learning activities. Moreover, the context of this study focused on developing instructional materials at the primary school level remains underexplored in educational development research. Thus, this study may serve as a reference for broader international mathematics education, particularly since PMRI aligns closely with the principles of Realistic Mathematics Education (RME).